The Influence of Internal and External Factors on Liquidity Risk Sharia Rural Bank in Indonesia for The Period 2019-2024 - Nurzanah, Anita Zahra; Tamara, Destian Arshad Darulmalshah; Qolbi, Satria Kharimul; Ilmi, Muhammad Bakhrul (Indonesian Journal of Economics and Management, 2024)
This study investigates how, from 2019 to 2020, internal factors such as Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), and Cash Ratio (CR) as well as external factors such as the BI-rate and inflation affect liquidity risk measured by the Financing to Deposit Ratio (FDR). Dynamic panel data analysis using the System Generalized Method of Moments (SYS-GMM) approach to address data dynamics and endogeneity. This study uses secondary data from the Financial Ratio Publication Report of Sharia Rural Bank, published by the Financial Services Authority and displayed on the official Bank Indonesia website, which consists of 153 Sharia Rural Bank. The results show that internal and external factors have a significant impact on the liquidity risk of Sharia Rural Bank. This study concludes that liquidity management must adapt to market conditions and capital resilience. Strategic recommendations are provided to enhance financing oversight, maintain capital adequacy, and improve cash management effectiveness.